A study on the determination of reserpine in tablets - Pun, Daniel; Cruz, Ileana R. (Manila Department of Pharmaceutical Chemistry, College of Pharmacy, University of the Philippines, 1989)
A proposed colorimetric procedure for the assay of reserpine in tablet dosage form is presented. This method involves the coupling of vanillin with the saponified alkaloid and subsequent measurement by spectrophometric means. Other methods, official or non-official, as well as newer approaches are reviewed and their procedures evaluated. It is the hope, that this paper will give a closer look on the development of an assay on reserpine, especially on its extraction and determination.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, February 1989.
Keywords: Reserpine